Keputusan Pembelian Berbasis Produk, Harga, dan Lokasi - Zannubha Fuzi Afifah; Sudarijati Sudarijati; Titiek Tjahja Andari (Journal Economic Excellence Ibnu Sina, 2023)
Researched analyzes the effect of product, price, and location has a positive and significant effect on purchasing decisions using non-probability sampling techniques, purposive sample methods, research designs namely verification and descriptive methods. The analysis used is multiple linear regression analysis. As for the research results product, price, and location simultaneously and partially have a positive & significant effect on purchasing decisions.